Designing a Strategic Model for Entrepreneurship Development with a Value-Enhancement Approach in Small and Medium-Sized Enterprises in the Industrial Parks of Sistan and Baluchestan Province - Armanmehr, Navid; Naseri, Bahareh; Pourshahabi, Vahid (Management Strategies and Engineering Sciences, 2025)
The main objective of this research is to design a strategic model for entrepreneurship development with a value-enhancement approach in small and medium-sized enterprises (SMEs) in the industrial parks of Sistan and Baluchestan Province. This study is applied in terms of its objective and qualitative in terms of its method. The statistical population consisted of all university professors and senior managers of small and medium-sized enterprises in the industrial parks of Sistan and Baluchestan Province, from which 17 individuals were purposefully selected. This selection was based on the individuals' experience and expertise in entrepreneurship, and a snowball sampling method was also employed to broaden the scope of opinions and experiences. The data were analyzed using thematic analysis. Subsequently, the Content Validity Ratio (CVR) index was used to assess and validate the relative content coefficient of each theme. The results of the thematic analysis revealed 19 basic themes, 6 organizing themes, and 1 overarching theme, which were presented in the form of a thematic network as a model. The key elements of the model included "industry analysis," "evaluation of internal capabilities," "determination of strategic solutions," "strategy implementation," "strategy evaluation and improvement," and "entrepreneurial knowledge and skill development."